Luminescence thermometry for in situ temperature measurements in microfluidic devices. Issue 7 (28th February 2019) - Geitenbeek, Robin G.; Vollenbroek, Jeroen C.; Weijgertze, Hannah M. H.; Tregouet, Corentin B. M.; Nieuwelink, Anne-Eva; Kennedy, Chris L.; Weckhuysen, Bert M.; Lohse, Detlef; van Blaaderen, Alfons; van den Berg, Albert; Odijk, Mathieu; Meijerink, Andries
Abstract : In this work we present 3 showcases that luminescence thermometry is a promising and versatile technique for temperature monitoring in various microfluidic devices. Abstract : Temperature control for lab-on-a-chip devices has resulted in the broad applicability of microfluidics to, e.g., polymerase chain reaction (PCR), temperature gradient focusing for electrophoresis, and colloidal particle synthesis. However, currently temperature sensors on microfluidic chips either probe temperatures outside the channel (resistance temperature detector, RTD) or are limited in both the temperature range and sensitivity in the case of organic dyes. In this work, we introduce ratiometric bandshape luminescence thermometry in which thermally coupled levels of Er 3+ in NaYF4 nanoparticles are used as a promising method for in situ temperature mapping in microfluidic systems. The results, obtained with three types of microfluidic devices, demonstrate that temperature can be monitored inside a microfluidic channel accurately (0.34 °C) up to at least 120 °C with a spot size of ca. 1 mm using simple fiber optics. Higher spatial resolution can be realized by combining luminescence thermometry with confocal microscopy, resulting in a spot size of ca. 9 μm. Further improvement is anticipated to enhance the spatial resolution and allow for 3D temperature profiling.